Promoting Tuber Formation In Vitro with Benzyl Amino Purine and Paclobutrazol at Different Concentrations - Suharjo, Usman Kris Joko; Hasanudin, Hasanudin; Pamekas, Tunjung; Pujiwati, Hesti; Vanturini, Alyi (Akta Agrosia, 2019)
A common problem related to the production of potatoes in Indonesia is the use of poor quality seed sources and declining seeds. Plant tissue culture is one of the best methods used for the provision of quality seeds. This study aims to establish the best combination of BAP concentration and the concentration of paclobutrazol in spurring the growth of cuttings and initiation of potato tubers in vitro.This research was conducted in November 2017 until June 2018 at Agronomy Laboratory of Biotechnology Division and Plant Culture Network of Agriculture Faculty of Bengkulu University. The  research  design  used  was  Completely  Randomized  Design  (CRD)  which  consist  of  18 combination of BAP treatment and Paclobutrazol was repeated 6 times. The concentration of BAP used was 0 mg / l, 5 mg / l, 10 mg / l and the concentration of Paclobutrazol 0 mg / l; 2.5 mg / l; 5 mg / l; 7.5 mg / l; 10 mg / l; 12.5 mg / l. The data of the research were analyzed by F test of 5% level and if there were different between treatments followed by Duncan's Multiple Range Test (DMRT) test of5% level. The results showed that the combination of BAP and  Paclobutrazol concentration had significant effect on all observed variables. Treatment of 5 mg / l BAP and 7.5 mg / l Paclobutrazol is the best medium in inducing potato micro tube as indicated by the fastest tuber formation time, highest percentage of productive crops, largest number of tubers per bottle, number of tubers per productive plant, tuber diameter the largest and highest wet weight of tuber per bottle. Keywords : in vitro, BAP, paclobutrazol, Potato